Peran JAKI sebagai Super App dalam Meningkatkan Tata Kelola Digital Jakarta: Evaluasi Kualitas Sistem, Informasi, dan Layanan serta Kesejahteraan Masyarakat - Muhammad Naufal Helga Fikri; Sulis Ariska Novrianti; Oktaviani Rosmala; Herie Saksono (Research and Development Agency Ministry of Home Affairs, 2026)
This study evaluates the effectiveness of super-app-based digital governance, focusing on Jakarta Kini (JAKI) as an integrated public-service platform. Despite the proliferation of over 27,000 government applications in Indonesia, which has produced systemic inefficiencies and fragmented services, comprehensive evaluations linking digital-service performance, bureaucratic integration, and public well-being remain limited in the academic literature. This research addresses that gap by analyzing the interrelationships among digital-service quality—system, information, and service quality—user satisfaction, and public well-being, while considering the role of bureaucratic integration within the JAKI ecosystem. Employing a secondary data analysis method, the study synthesizes information from the JAKI service database, official government documents, media reports, and scientific publications to identify institutional patterns and dynamics of digital governance. The findings indicate that system, information, and service quality are associated with user satisfaction, which in turn relates to public well-being, as measured by perception, participation, and acceptability. However, bureaucratic fragmentation, regulatory inconsistencies, and the absence of a unified governance framework emerge as significant impediments to optimizing digital-service integration. These insights underscore that effective digital services require robust institutional alignment and coherent governance. Theoretically, the study integrates the information systems success model with a well-being approach to digital governance, underscoring the importance of coherent policy, cross-sectoral governance harmonization, and inclusive digital literacy to maximize the impact of digital public services.